Surgical Removal of Migrated Coil after Embolization of Jejunal Variceal Bleeding: A Case Report - Junhwan Kim; Danbi Lee; Kyunghwan Oh; Mingee Lee; Seol So; Dong-Hoon Yang; Chan-Wook Kim; Dong Il Gwon; Young-Hwa Chung (The Korean Journal of Gastroenterology, 2017)
Jejunal variceal bleeding is less common compared with esophagogastric varices in patients with portal hypertension. However, jejunal variceal bleeding can be fatal without treatment. Treatments include surgery, transjugular intrahepatic porto-systemic shunt (TIPS), endoscopic sclerotherapy, percutaneous coil embolization, and balloon-occluded retrograde transvenous obliteration (BRTO). Percutaneous coil embolization can be considered as an alternative treatment option for those where endoscopic sclerotherapy, surgery, TIPS or BRTO are not possible. Complications of percutaneous coil embolization have been reported, including coil migration. Herein, we report a case of migration of the coil into the jejunal lumen after percutaneous coil embolization for jejunal variceal bleeding. The migrated coil was successfully removed using surgery.